Transformasi Komisi Nasional Hak Asasi Manusia Sebagai Lembaga Superbody Dalam Pelanggaran HAM Berat Di Indonesia - Tauba Zaka Adkia; Agus Riewanto; Achmad Achmad (Res Publica: Jurnal Hukum Kebijakan Publik, 2026)
Gross human rights violations in Indonesia have persistently faced structural obstacles, particularly due to the limited authority of the National Commission on Human Rights (Komnas HAM) and the dominant role of the Attorney General’s Office (Jaksa Agung). Although Komnas HAM is constitutionally mandated to conduct inquiries into gross human rights violations, its findings often fail to translate into effective prosecution, as evidenced by the practice of indicting only individual perpetrators while neglecting structural or command responsibility. This condition not only weakens inter-institutional coordination but also undermines accountability for gross human rights violations. This paper aims to analyze the institutional design governing Komnas HAM’s authority in handling gross human rights violations and to examine how the imbalance of power between Komnas HAM and the Attorney General’s Office (Jaksa Agung) affects the effectiveness of the human rights justice process. The study further seeks to formulate a model for strengthening Komnas HAM’s independence to ensure meaningful accountability. This research employs a normative juridical method with a statutory, conceptual, and case-based approach, focusing on Law No. 39 of 1999 on Human Rights and Law No. 26 of 2000 on Human Rights Courts, as well as selected gross human rights cases adjudicated in Indonesia. The findings indicate that Komnas HAM’s subordinate position in the criminal justice process contributes to fragmented prosecutions and the non-fulfillment of victims rights. Accordingly, this paper argues for institutional reform through the enhancement of Komnas HAM’s authority and procedural standing to strengthen accountability mechanisms for gross human rights violations in Indonesia.